Neutrino oscillation studies with IceCube-DeepCore - Aartsen, M. G.; Abraham, K.; Ackermann, Markus; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Anderson, T.; Ansseau, I.; Archinger, M.; Arguelles, C.; et al. (Deutsches Elektronen-Synchrotron, DESY, Hamburg, 2016)
Nuclear physics / B 908, 161 - 177(2016). doi:10.1016/j.nuclphysb.2016.03.028 : IceCube, a gigaton-scale neutrino detector located at the South Pole, was primarily designed to search for astrophysical neutrinos with energies of PeV and higher. This goal has been achieved with the detection of the highest energy neutrinos to date. At the other end of the energy spectrum, the DeepCore extension lowers the energy threshold of the detector to approximately 10 GeV and opens the door for oscillation studies using atmospheric neutrinos. An analysis of the disappearance of these neutrinos has been completed, with the results produced being complementary with dedicated oscillation experiments. Following a review of the detector principle and performance, the method used to make these calculations, as well as the results, is detailed. Finally, the future prospects of IceCube-DeepCore and the next generation of neutrino experiments at the South Pole (IceCube-Gen2, specifically the PINGU sub-detector) are briefly discussed. : Published by North-Holland Publ. Co., Amsterdam